'Neo-agents': A study of village governance under the 'Projects to Villages' model. (July 2018) - Li, Zupei
The program 'Projects to Villages' ( xiangmu jincun ) is an important means by which the Chinese government distributes resources to grassroots villages, and it has gained popularity in recent years. 'Projects to Villages' has introduced a new group of players into the village governance body—village cadres designated in this study as 'neo-agents'. The term explains a newly emerged grassroots power base that was created by the government's 'Projects to Villages' initiatives. With the intense competition for projects among villages, people with the right political and personal skills, broad networks, and less vested interest in the village have been able to step onto the political stage and gain power. Contrary to the essential need for developing long-term effective rural leadership, these neo-agents practice a type of short-term, interest-focused governance. They do not provide a solution to the governance quandary experienced in villages since the rural taxation reform in 2002; instead, given the availability of state resources, they help further consolidate the existing village power structure. The study also compares neo-agents with the traditional power agents of gentry, local elites, and government officials. Four aspects of governance, including foundation of authority, mechanism of power transfer, structure of governance, and effectiveness of governance are discussed in hopes of stimulating further academic and practical interest in the subject.